Case Report: Pathogenesis With a Rare RHOA A161E Mutation in a Patient With Angioimmunoblastic T-Cell Lymphoma - Cao, Lihong; Tong, Hongyan; Liu, Xing; Xu, Yingqing; Yu, Fang; Pan, Qi; Lai, Jin; Huang, Jian; Qin, Jiayue; Jin, Jie (Frontiers in Genetics, 2022)
Angioimmunoblastic T-cell lymphoma (AITL) genomic abnormalities are highly disease-specific and the ras homology family member A (RHOA) gene is one of the most recurrent mutated genes, especially for RHOA G17V mutation site. Here, we identified a rare RHOA A161E mutation in an AITL patient through gene sequencing platforms. The patient presented with persistent hypereosinophilia, asymptomatic or symptomatic mildly for over three years. At diagnosis, this patient manifested night sweats, weight loss, multiple lymphadenopathies, enlargement of liver and spleen. We performed a retrospective genetic mutation analysis by whole exome sequencing (WES) and droplet digital PCR (ddPCR) on serial gastric, intestinal and lymph node specimens. The genetic mutation testing result demonstrated that a rare RHOA A161E mutation was found, which was elevated significantly on diagnosis related to AITL pathogenesis. Our case confirms that genetic mutation testing is helpful for diagnostic classification in AITL and dynamic monitoring gene mutations at multiple time points may facilitate early detection of disease diagnosis.